Pengaturan Pemeriksaan Setempat (decentee) Dalam Peraturan Perundang-Undangan Di Indonesia - Maria Rosalina (Universitas Islam Sumatera Utara, 2018)
AbstractProof is one of the important and decisive stages in the trial process in civil procedural law because the result of this verification can be used by judges, who try cases in providing legal considerations to make decisions, so that the judges can make decisions based on real legal facts, and provide legal satisfaction to justice seekers. One of the proofs used by judges in the trial is the local examination (decentee). However, this local examination is not included in the evidence set by Article 1866 of the Civil Code and Article 164 HIR / Article 284 of the RBG, namely proof of letters, evidence of witnesses, allegations, confessions, and oaths. Based on this, it raises problems, namely how to regulate the local examination in the legislation in Indonesia, who can request a local examination, and what obstacles are encountered when the local examination is carried out. Keywords: regulation, local examination, legislation